2021
DOI: 10.1186/s13054-021-03802-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of extubation outcome in critically ill patients: a systematic review and meta-analysis

Abstract: Background Extubation failure is an important issue in ventilated patients and its risk factors remain a matter of research. We conducted a systematic review and meta-analysis to explore factors associated with extubation failure in ventilated patients who passed a spontaneous breathing trial and underwent planned extubation. This systematic review was registered in PROPERO with the Registration ID CRD42019137003. Methods We searched the PubMed, We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 88 publications
3
50
0
7
Order By: Relevance
“…The most important features included PaO 2 (minimum), respiratory failure, PaO 2 (final), ventilation time, and the SOFA score (24 h). These results were consistent with other studies (29,30). Torrini et al (30) conducted a meta-analysis, and the results indicated that history of respiratory disease, duration of mechanical ventilation, and a lower PaO 2 /fraction of inspired oxygen After weaning from mechanical ventilation and extubation, such patients may experience severe deoxygenation (31).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The most important features included PaO 2 (minimum), respiratory failure, PaO 2 (final), ventilation time, and the SOFA score (24 h). These results were consistent with other studies (29,30). Torrini et al (30) conducted a meta-analysis, and the results indicated that history of respiratory disease, duration of mechanical ventilation, and a lower PaO 2 /fraction of inspired oxygen After weaning from mechanical ventilation and extubation, such patients may experience severe deoxygenation (31).…”
Section: Discussionsupporting
confidence: 84%
“…These results were consistent with other studies (29,30). Torrini et al (30) conducted a meta-analysis, and the results indicated that history of respiratory disease, duration of mechanical ventilation, and a lower PaO 2 /fraction of inspired oxygen After weaning from mechanical ventilation and extubation, such patients may experience severe deoxygenation (31). Patients with a long mechanical time tend to have more severe disease.…”
Section: Discussionsupporting
confidence: 83%
“…First, the study is a retrospective observational study, when considering the findings, its post hoc nature should be taken into account. Despite the confounders adjusted, several residual potential confounders may also influence extubation failure based on the plurality of often-intertwined mechanisms, such as the respiratory, circulatory, and neurological functions [ 27 ]. Second, the generalizability of the study may be in question because it was conducted at a single tertiary care hospital.…”
Section: Discussionmentioning
confidence: 99%
“…(ver Figura 2), cifra que coincide con la descrita en la literatura la cual varía entre 10 a 20% de pacientes intubados 3,8,13,28 . Estos datos indican que el evento sigue siendo frecuente en esta población y que se necesita más investigación sobre las intervenciones que puedan reducir su impacto, tales como reducir al mínimo necesario la duración de la intubación, el puente temprano hacia estrategias como Ventilación mécanica no invasiva o Cánula nasal de alto flujo, y desarrollar herramientas adicionales que permitan predecirla y reducirla 12,29 .…”
Section: Discussionunclassified